Trade liberalization and manufacturing productivity changes in Korea during the past three decades - Yeongkwan Song (Korea Development Institute (KDI), 2020)
One of the key goals of trade policy, which includes FTAs, should be the enhancement of productivity in the overall economy through the improved productivity of the tradable sector. This can be achieved by enhancing the productivity of existing firms, and eliminating lowproductivity firms to improve overall industrial productivity. This study examines the effects of Korea's trade policies in terms of bolstering the productivity of existing firms in the tradable sector. It shows that Korea's FTAs with major trade partners, such as the EU, US and China, have failed to provide meaningful impetus. As for raising productivity through firm exits, this study confirms that it has a positive impact on raising total factor productivity (TFP) across industry. However, further studies are needed to substantiate that this is owed to trade liberalization. To raise overall economic productivity, future trade policies should be designed to enhance the productivity of existing firms, and expel those with low productivity. A trade policy-driven expansion of imports and exports could brighten the prospects for the tradable sector, encouraging firms to boost productivity. It is imperative that efforts are made to increase the positive effects of trade liberalization and minimize the negative effects on society by shifting the focus of the current Trade Adjustment Assistance system towards supporting workers instead of firms, and improving retraining and vocational programs for the unemployed, among others.
Keywords: 330; Handelsliberalisierung; Freihandelsabkommen; Produktivität; Industrie; Südkorea